Development and Validation of Spectrophotometric Methods for the Determination of Amoxicillin trihydrate and Dicloxacillin sodium in Their Binary Mixture. Issue 6 (2nd November 2018) - Naguib, Ibrahim A.; Abdelaleem, Eglal A.; Zaazaa, Hala E.; Hussein, Essraa A.; Alsalahat, Izzeddin
Abstract: Three sensitive and cost-effective spectrophotometric methods are introduced for the determination of amoxicillin and dicloxacillin in their binary mixtures with minimum sample pretreatment, with or without the presence of their common impurity; 6-aminopenicillanic acid (6-APA). In this work, dicloxacillin is determined by dual wavelength, derivative ratio and isoabsorptive spectrophotometric methods. However, amoxicillin is determined by direct UV spectrophotometry at 273.6 nm and by the first derivative ratio spectrophotometric method (DD method). For method (A); the dual wavelength method, the wavelengths selected for the determination of dicloxacillin were 223.6 and 237 nm. Method (B); the isoabsorptive spectrophotometric method, comprises measuring the total content of the mixture at their isoabsorptive point (230.4 nm), and then the content of dicloxacillin can be calculated by subtraction. Method (C) is the first derivative of ratio spectra for the determination of amoxicillin (using 8 μg/mL of dicloxacillin as a divisor at 231 nm) and dicloxacillin (using 20 μg/mL of 6-APA as a divisor at 234.6 nm) in presence of their common impurity; 6-APA. Statistical comparison of the results obtained from the suggested methods with those of the reported HPLC method showed no significant difference with respect to accuracy and precision. The developed methods can be used for quality control analysis of the studied drugs in laboratories lacking HPLC qualifications. Kay words: Amoxicillin, Dicloxacillin, Dual wavelength, Isoabsorptive point, First derivative ratio